SHORT COMMUNICATION: KANDUNGAN KIMIA MINYAK ATSIRI RIMPANG TUMBUHAN Alpinia malaccensis - Jismi Mubarrak (Universitas Khairun, 2017)
Alpinia malaccencis is a plant of the family Zingiberaceae which is widely used as an antibacterial, antifungal, antimutagen and antioxidants. Especially on the genus Alpinia, generally produce essential oils. This study focused on identifying the chemical compounds of essential oils from rhizome Alpinia malaccencis. To obtain essential oils from plants was done by microhidro distillation method. A total of 100 grams of plant roots Alpinia malaccencis cut into small pieces about the size of 1 cm and distilled at a temperature of 100 0C using micro hidro distillation in waves of 500 watts. Results obtained in the form of essential oil scented translucent color typical of this plant. Results of analysis Gas Chromatography-Mass Spectroscopy (GC-MS) of essential oils based on Similarities Index (SI) compounds include: α-Pinen, β-pinene, 1,8-cineol, 3-Pinanon, α-Terpineol, chavicol, Methyl chavicol, eugenol, O-Methyl eugenol, methyl cinnamic, Cumin aldehyde.Key word : Alpinia malacencis, Esential oil